The sesquiterpenoid valerenic acid protects neuronal cells from the detrimental effects of the fungicide benomyl on apoptosis and DNA oxidation - Kara, Mehtap; Öztaş, Ezgi; Boran, Tuğçe; Sevim, Çiğdem; Keskin, Seda Eren; Veskoukis, Aristidis S; Kuzmin, Sergei V; Tsatsakis, Aristides M (SAGE Publications, 2022)
Background Valerenic acid (VA), a sesquiterpenoid of the plant Valeriana officinalis, has attracted attention of the research community due to its potential positive role against neurodegenerative diseases induced by chemicals. However, the relevant evidence in the literature is scarce. Therefore, this study aimed to examine the putative protective role of VA on the toxic effects of the fungicide benomyl on SH-SY5Y neural cells. Methods Cell viability was determined via the MTT and NRU assays, DNA damage was assessed via comet assay and apoptosis was evaluated through the expression of relevant genes. Results According to the results, exposure of the cells to benomyl enhanced viability inhibition and promoted DNA damage and apoptosis since the expression levels of the genes coding for MAPK8, NF-kB, Bax, Caspase-9 and Caspase-3 were increased. Treatment of the cells with VA ameliorated these effects in a concentration dependent manner. Conclusion It is concluded that the molecular mechanism through which benomyl exerts its toxic action appears to depend on DNA oxidation and apoptosis induction. Furthermore, VA, a plant-derived compound is a protective antioxidant against pesticide-induced toxicity. Therefore, herbs, extracts and compounds of plant origin could be used as nutritional supplements that back up the beneficial role of medicine in neurodegenerative diseases.
Keywords: Neuroblastoma; Indenes; Humans; Apoptosis; Benomyl; DNA; Sesquiterpenes; Fungicides, Industrial; 3. Good health